Survey on bagasse cogeneration in sugar plants of north Karnataka - Mahesh G. Emmi, Mr.; Aravindrao M. Yadwad, Dr.; Vinay V. Kuppast, Dr.; Sampanna M, Dr. (International Journal of Engineering and Technology, 2018)
Cogeneration is the idea of converting two forms of energy from one fuel. In the sugar industry from bagasse two forms con- verted are heat and electrical power. The sugar industries utilise bagasse to generate power and to operate the plant . Here the bagasse serves as a fuel to the Boiler and this power consumption is known as captive power generation. The so generated power will be more than the power required for the running of the industry. The remaining excess power can be fed to the power grid as a power export.The actual site survey of different bagasse cogeneration plants has been carried out and included in this review. Also, this paper reviews the performance of the bagasse cogeneration plants all over the world. The review includes not only study on the power genera- tion plants but also throws an insight to identify the scope for the study on the performances of the cogeneration plants in Karnataka based on the global perview. The effective and efficient utilisation of the bagasse cogeneration plants could be identified for the im- provement of the performance of the cogeneration plants and also the economics of running a sugar industry.
Keywords: Bagasse Cogeneration; Power Grid; Sugar Plants.